2011
DOI: 10.1007/s10549-011-1795-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial comparing advanced pneumatic truncal, chest, and arm treatment to arm treatment only in self-care of arm lymphedema

Abstract: Treatment of the truncal lymphatics prior to treatment of the lymphedematous arm is an accepted, although not empirically tested, therapeutic intervention delivered during decongestive lymphatic therapy (DLT). Breast cancer survivors with arm lymphedema are encouraged to use these techniques when performing simple lymphatic drainage as part of their life-long lymphedema self-care. Self-massage is at times difficult and pneumatic compression devices are used by many patients to assist with self-care. One such d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The effect of dominance has previously been found for other tools used in the diagnosis of lymphedema such as bioimpedance spectroscopy which has necessitated different cut-offs depending on which limb was at risk. 24,25,28 It is therefore logical that circumference and volume cut-offs should also take into account limb dominance.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of dominance has previously been found for other tools used in the diagnosis of lymphedema such as bioimpedance spectroscopy which has necessitated different cut-offs depending on which limb was at risk. 24,25,28 It is therefore logical that circumference and volume cut-offs should also take into account limb dominance.…”
Section: Discussionmentioning
confidence: 99%
“…The revised 36-item tool was subsequently validated [3,8,11,12,19,20]. (Figure 1) Breast cancer survivors with previously diagnosed lymphedema completed the LSIDS-A using the 1-10 scale in addition to other measures used to evaluate validity and reliability.…”
Section: Methodsmentioning
confidence: 99%
“…In a small pre-and post-test study of 21 breast cancer survivors with lymphedema, Moattari et al (2012) reported a significant effect of combined CDT and pneumatic compression device on arm volume reduction (p < 0.05). A small RCT in the United States assigned 42 breast cancer survivors with lymphedema into an experimental group receiving truncal, chest, and arm pneumatic compression to treat lymphedema and a control group of arm compression only (Ridner, Murphy, et al, 2012). Findings demonstrated no significant effect of the pneumatic compression device on lymphedema symptoms, bioimpedance ratio, and physical functioning.…”
Section: Effectiveness Not Establishedmentioning
confidence: 99%